Comparing oncoplastic breast conserving surgery with mastectomy and immediate breast reconstruction: Case-matched patient reported outcomes. Issue 10 (October 2017) - Kelsall, Jennett E.; McCulley, Stephen J.; Brock, Lisa; Akerlund, Malin T.E.; Macmillan, R. Douglas
Summary: Background: Oncoplastic breast conserving surgery (OBCS) allows women who may otherwise have mastectomy and immediate reconstruction (MxIR) the choice to conserve their breast yet avoid deformity. We compared the outcome of these options. Methods: Two cohorts meeting study criteria were identified from prospectively audited series of women undergoing OBCS or MxIR. After case matching for age, tumour size and date of surgery, stratification by breast size and controlling for radiotherapy; body image scale (BIS) scores of psychosocial function and patient reported outcome measures (PROMs) for breast appearance and return to function were analysed. Results: A total of 567 women (286 treated by OBCS and 281 by MxIR) fulfilled inclusion criteria. Demographics were similar between the two unmatched cohorts, except for radiotherapy, age and tumour size (all p < 0.001). Overall, BIS score (p = 0.002), self-rated breast appearance, return to work and function (all p < 0.001) significantly favoured OBCS. Case-matched women with larger breasts treated by OBCS reported better BIS scores (mean 3.30 vs. 5.37, p = 0.011) and self-rated breast appearance score (p < 0.001) than MxIR, whereas no significant difference was observed for smaller breasts. BIS and appearance favoured OBCS, regardless of whether radiotherapy would have been avoided if treated by MxIR. Conclusion: OBCS offers suitable women the option to avoid MxIR while providing faster recovery. Better psychosocial and self-rated satisfaction with breast appearance is achieved for OBCS in all groups, regardless of the need for radiotherapy, apart from those women with smaller breasts for whom the results are comparable.